Practice guideline summary: Reducing brain injury following cardiopulmonary resuscitation. (30th May 2017) - Geocadin, Romergryko G.; Wijdicks, Eelco; Armstrong, Melissa J.; Damian, Maxwell; Mayer, Stephan A.; Ornato, Joseph P.; Rabinstein, Alejandro; Suarez, José I.; Torbey, Michel T.; Dubinsky, Richard M.; Lazarou, Jason
Abstract : Objective: To assess the evidence and make evidence-based recommendations for acute interventions to reduce brain injury in adult patients who are comatose after successful cardiopulmonary resuscitation. Methods: Published literature from 1966 to August 29, 2016, was reviewed with evidence-based classification of relevant articles. Results and recommendations: For patients who are comatose in whom the initial cardiac rhythm is either pulseless ventricular tachycardia (VT) or ventricular fibrillation (VF) after out-of-hospital cardiac arrest (OHCA), therapeutic hypothermia (TH; 32–34°C for 24 hours) is highly likely to be effective in improving functional neurologic outcome and survival compared with non-TH and should be offered (Level A). For patients who are comatose in whom the initial cardiac rhythm is either VT/VF or asystole/pulseless electrical activity (PEA) after OHCA, targeted temperature management (36°C for 24 hours, followed by 8 hours of rewarming to 37°C, and temperature maintenance below 37.5°C until 72 hours) is likely as effective as TH and is an acceptable alternative (Level B). For patients who are comatose with an initial rhythm of PEA/asystole, TH possibly improves survival and functional neurologic outcome at discharge vs standard care and may be offered (Level C). Prehospital cooling as an adjunct to TH is highly likely to be ineffective in further improving neurologic outcome and survival and should not be offered (Level A). Other pharmacologic and nonpharmacologic strategies (applied with or without concomitant TH) are also reviewed.